Statistical analysis of parameters ACK_Timeout, CTS_Timeout and SLOT_Time links in long distance 802.11g (Revista de Investigaciones Universidad del Quindío, 2014)
This project proposes to use as end the communication protocol 802.11g, considering its limitations, to improve data transmission capability constituents varying technology parameters such as the CTS/RTS, and ACK Time out SLOTTIME according to both the capacity and transmission speed. For this recent work consisted of defining four scenaries where later measurements transfer rate were performed, the samples obtained in each scenario were analyzed by means of statistical Kolmogorov- Smirnov and probability distributions of found tabular data with a simpler interpretation of these forces and thus the maximum amount of information that identifies the values that maximize the transfer rate is acquired.It is observed that most of the data distributions of each parameter are of uniform type, therefore, reaching values higher transfer exhibit a wide range around the average, which shows that the parameter setting ACK Time Out is significant in terms of performance since its variation can produce the most critical points of the connection. Proper adjustment of these parameters also allows checking that IEEE802.11g is suitable when applied to long distances, especially in remote rural areas with low population density, as speeds got up to 19 Mbps that are suitable for linking several kilometers with good quality.
Keywords: ACK Time Out; CTS Time Out; Slot TimeIEEE802.11g; Link; Kolmogorov-Smirnov